2017
DOI: 10.3847/1538-4357/aa6890
|View full text |Cite
|
Sign up to set email alerts
|

Swift Monitoring of NGC 4151: Evidence for a Second X-Ray/UV Reprocessing

Abstract: Swift monitoring of NGC 4151 with an∼6hr sampling over a total of 69 days in early 2016 is used to construct light curves covering five bands in the X-rays (0.3-50keV) and six in the ultraviolet (UV)/optical (1900-5500Å). The three hardest X-ray bands (>2.5keV) are all strongly correlated with no measurable interband lag,while the two softer bands show lower variability and weaker correlations. The UV/optical bands are significantly correlated with the X-rays, lagging ∼3-4days behind the hard X-rays. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
176
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(193 citation statements)
references
References 67 publications
16
176
1
Order By: Relevance
“…Although the X-ray light curve would be expected to be smoothed if reprocessed at UV wavelengths, comparison of Figures 3 and the Appendix shows that the inferred driving light curve does not correlate very well with the observed X-ray variations (this is confirmed by the ICCF analysis from Section 3). This poor correlation was also seen in 2013 by Shappee et al (2014), and has been observed in other objects, including NGC 5548 (Uttley et al 2003;Edelson et al 2015), MR 2251-178 (Arévalo et al 2008), Mrk 79 (Breedt et al 2009), NGC 3783 ), and NGC 4151 (Edelson et al 2017). Several of these studies have been unable to represent the UV/optical light curves as a reprocessed (smoothed and shifted) version of the X-ray light curve (Arévalo et al 2008;Breedt et al 2009;Starkey et al 2017), which is problematic for a generic disk reprocessing model.…”
Section: Challenges To the Disk Reprocessing Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the X-ray light curve would be expected to be smoothed if reprocessed at UV wavelengths, comparison of Figures 3 and the Appendix shows that the inferred driving light curve does not correlate very well with the observed X-ray variations (this is confirmed by the ICCF analysis from Section 3). This poor correlation was also seen in 2013 by Shappee et al (2014), and has been observed in other objects, including NGC 5548 (Uttley et al 2003;Edelson et al 2015), MR 2251-178 (Arévalo et al 2008), Mrk 79 (Breedt et al 2009), NGC 3783 ), and NGC 4151 (Edelson et al 2017). Several of these studies have been unable to represent the UV/optical light curves as a reprocessed (smoothed and shifted) version of the X-ray light curve (Arévalo et al 2008;Breedt et al 2009;Starkey et al 2017), which is problematic for a generic disk reprocessing model.…”
Section: Challenges To the Disk Reprocessing Modelmentioning
confidence: 94%
“…However, microlensing can only probe the disks in distant, high-luminosity quasars, while RM provides a means of probing accretion disks in local, low-luminosity AGN. It is therefore imperative to expand the sample of objects with secure interband continuum lags, and several such programs have been completed, with others still in progress (e.g., NGC 4151, Edelson et al 2017;NGC 4593, McHardy et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the data have often suffered from poor temporal sampling (given the short lags), leading to large uncertainties in the lag. Several recent observing campaigns have changed this (McHardy et al 2014;Shappee et al 2014;Edelson et al 2015;Fausnaugh et al 2016;Edelson et al 2017). In particular, the AGN STORM campaign on NGC5548 used a combination of monitoring with the Hubble Space Telescope (HST) and the Neil Gehrels Swift Observatory (Swift hereafter), obtaining 282 observations over 125 days, with a mean sampling rate of less than 0.5 days (Edelson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, a high-cadence Swift monitoring campaign of the bright AGN NGC 4151 took place (Edelson et al 2017), with a sampling rate of approximately 6 hr over a 69day period. Here, the X-ray/UV/optical light curves are all well correlated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation